An innovative approach for estimating the number of tags in RFID traffic monitoring systems - Chebil, Jalel; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (IEEE, 2024)
Intelligent transport systems (ITS) playa pivotal role in enhancing traffic control by leveraging advanced technologies to optimize traffic flow, reduce congestion, and improve overall transportation efficiency. One of the technologies used in ITS is Radio Frequency Identification (RFID) system for traffic monitoring and electronic toll collection. During identification process, RFID systems encounter two main challenges: tag collision and reader collision. This paper presents a new approach to estimate the number of tags within the reader's range in an RFID traffic monitoring system, with the goal of improving the dynamic framed slotted ALOHA anti-collision algorithm. Simulation results showed that although the proposed approach did not demonstrate substantial enhancement in system efficiency compared to Schoute method, it significantly decrease system delay, especially under higher tag numbers.